2010
DOI: 10.1086/654815
|View full text |Cite
|
Sign up to set email alerts
|

On the Cytoadhesion ofPlasmodium vivax–Infected Erythrocytes

Abstract: These observations prompt a modification of the current paradigms of the pathogenesis of malaria and clear the way to investigate the pathophysiology of P. vivax infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
265
1
28

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(307 citation statements)
references
References 35 publications
13
265
1
28
Order By: Relevance
“…25 In addition, recent studies report cytoadherence of P. vivax-infected erythrocytes to endothelial receptors. 26 Furthermore, microrheologic research showed increased aggregation, agglutination, and reduction in deformability of P. vivax-infected erythrocytes. 27 Patients infected with P. vivax showed increased levels of interferon-γ and tumor necrosis factor showed a linear correlation with the possibility of developing severe malaria.…”
Section: Discussionmentioning
confidence: 99%
“…25 In addition, recent studies report cytoadherence of P. vivax-infected erythrocytes to endothelial receptors. 26 Furthermore, microrheologic research showed increased aggregation, agglutination, and reduction in deformability of P. vivax-infected erythrocytes. 27 Patients infected with P. vivax showed increased levels of interferon-γ and tumor necrosis factor showed a linear correlation with the possibility of developing severe malaria.…”
Section: Discussionmentioning
confidence: 99%
“…Os valores de HT, HB e do número de eritrócitos foram menores apenas nos indivíduos com alta carga parasitária, o que já é conhecido e descrito na literatura 17,23 . Sabe-se que o aumento da carga parasitária pode acarretar diminuição no número de GV, devido à ruptura dessas células durante os ciclos assexuados, ao sequestro de hemácias infectadas pelo baço e à formação de rosetas 27,28,29 .…”
Section: Discussionunclassified
“…Pregnant women are also more likely to experience relapses than non-pregnant ones [44]. P. vivax sequestration has been proposed [10], and recent reports indicate disproportional organ-specific and peripheral blood parasitaemia [42]. As for the dynamics of infection throughout pregnancy, no studies have addressed the issue.…”
Section: Dynamics Of Gestational and Placental Malariamentioning
confidence: 99%
“…In subsequent pregnancies, as immunity against placental-adherent strains develops, there is a reduced risk of adverse effects of malaria on the mother and fetus [6] and asymptomatic parasitaemia is common [7]. In the case of vivax malaria, with increasing reports of severe cases in Asia and South America [8,9], the consequences of infection during pregnancy remain to be elucidated, although adherence to endothelial cells [10] and sequestration of infected red blood cells in deep vasculature have been recently demonstrated [11,12].…”
Section: Introductionmentioning
confidence: 99%